Pengaruh Pola Pelapisan Isolator di Bagian Header Terhadap Temperatur Knalpot Sepeda Motor - Anas Mukhtar; Yanwar Prasetyo (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2022)
The heat of vehicle engine emission is still can be used in order to efficiency effort and thermal polution preventive activity. This research is aimed to get the effect of the insulator coating pattern on the header on the motorcycle exhaust temperature. The reserach is done for Honda Scoopy motorcycle with engine rotation vary as 1000, 1500 and 2000 rpm. Isolator insulation vary for insulation pattern as 0, 1 and 2 cm in distance. The temperatures of exhaust are measured in 4 points measurement with K type thermocouple. The result shows that insulator coating pattern affects the temperature of the exhaust gas heat dissipation exhaust pipe (header) motorcycle exhaust. Keywords: header, exhaust, isolator insulation, heat